Posmodernisme: Dampak dan Penerapannya pada Studi Islam - Ro'uf, Abdul Mukti (Analisis: Jurnal Studi Keislaman, 2019)
This paper concentrates on dialogue with postmodernism and religion while looking at some of the core ideas of postmodernism and the possibility of making it a reading tool for Islam, precisely for the benefit of Islamic studies, in contemporary society with its various implications. With the descriptive-analysis method this paper proves two things. First, that postmodernism as a movement of thought is not in direct contact with Islam. It is a response to the doctrine of modernism and traditional Christian doctrine. His criticism of religion is addressed to European Christians. However, the impact of his dissolution of value doctrine becomes nihilism, has disrupted the theological beliefs of religions, including Islam especially in the case of the spread of atheistic-inclined ideology. Secondly, as a critical philosophy, postmodernism contributes a deconstruction method to dismantle the establishment and the absoluteness of thought. In Islamic studies, the deconstructive approach is widely used by contemporary Islamic thinkers.